Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas